Upaya Peningkatan Aksesibilitas Geowisata Desa Jari melalui Pembuatan Papan Petunjuk Lokasi Geosite Selo Gajah & Banyu Wedang - Indriani, Yulia; Firmansyah, Hanif; Firmansyah, Ekananda Duta; Aji Kusumo, Dimas Priyo; Seldy, Seldy (Universitas Pahlawan Tuanku Tambusai, 2025)
Jari Village is a village in Gondang District, Bojonegoro Regency, East Java, which has two geosite sites. Both geosites have the potential to be developed into geotourism sites that can boost the economy of the surrounding community. However, their utilization has not been maximized due to low public awareness of the tourism economy. Through this Community Service Program (KKN) activity, Unigoro students encourage the community to have a greater sense of ownership of the earth heritage sites in their village. The KKN students plan to install geosite location signs to facilitate and complete the infrastructure for directions to the geosite location as an initial step in developing geotourism. The activity was carried out in Jari Village on August 31-7, 2025 through four stages: (1) survey of installation points, (2) preparation of tools and materials, (3) making and painting the boards, and (4) the installation process. The geosite location signboards are made of wood. Students utilize unused wood waste from one of the wood craftsmen in Jari Village to make geosite location signboards, thus supporting the concept of sustainability. The results of the activity show that the installation of signboards facilitates accessibility for the community and visitors to the geosite location while increasing public awareness of the village's geotourism potential. This activity is expected to be the first step in developing conservation-based tourism and encourage improvements to supporting infrastructure in the future.